2019
DOI: 10.1109/access.2019.2954650
|View full text |Cite
|
Sign up to set email alerts
|

User Acceptance of HUMP-Model: The Role of E-Mavenism and Polychronicity

Abstract: Social network site usage has grown to be a worldwide trend. These sites facilitate online contact between individuals having similar concerns. The speedy and extensive usage of such sites has affirmed their perception and positioning in the minds of users. This research adds to our consideration by empirically exploring determinants affecting users' acceptance of such sites. A HUMP model has been introduced to evaluate the effect of hedonic (perceived playfulness), utilitarian (perceived usefulness) e-mavenis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 100 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…There is a dearth of literature on market mavenism, and the current study was intended to add to the body of knowledge by examining this topic in a variety of domains. Reviewing earlier research on this subject revealed that a considerable number of prior studies suffer from a lack of generalizability as a result of the sampling strategy used, such as convenience sampling (non-probability sampling) or quota sampling [6,51,105,[118][119][120][121]. Due to the homogeneity of the samples, questions regarding external validity and the issue of self-selection bias may rise.…”
Section: -Discussion and Future Research Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a dearth of literature on market mavenism, and the current study was intended to add to the body of knowledge by examining this topic in a variety of domains. Reviewing earlier research on this subject revealed that a considerable number of prior studies suffer from a lack of generalizability as a result of the sampling strategy used, such as convenience sampling (non-probability sampling) or quota sampling [6,51,105,[118][119][120][121]. Due to the homogeneity of the samples, questions regarding external validity and the issue of self-selection bias may rise.…”
Section: -Discussion and Future Research Directionsmentioning
confidence: 99%
“…However, the influence of mavens on a variety of environmental and economic outputs -such as cross-store price savings, bargain proneness, sustainable consumption, and trip frequency -is the subject of further research [10]. Awais et al [6] reported that e-mavenism has a beneficial impact on sustainable consumption behavior, which helps marketers to better understand sustainable consumption behavior and enables opportunities to incorporate these structures into their strategies to gain a competitive advantage. Furthermore, market maven's influence diffusion processes [107].…”
Section: Figure 5 the Antecedents And Consequences Of Market Mavensmentioning
confidence: 99%
See 2 more Smart Citations
“…An online notion of the market mavens can be articulated as internet mavens [74]. "E-mavenism is one of the robust indicators on the intention to use and thus actual use of social networking sites" [75].…”
Section: E-mavenism and Frugalitymentioning
confidence: 99%